PENINGKATAN PEMBELAJARAN LOMPAT TINGGI MELALUI PERMAINAN SIRKUIT FORMULA 1 PADA SISWA KELAS V SD NEGERI SUKODONO 1 (Department of Physical Education, Sport, Health and Recreation, 2013)
Research purposes to determine the increase in the high jump lessons through the game of Formula 1 Circuit In Class V students of SD Negeri 1 Sukodono Jepara regency. Fifth grade students study subjects SD Negeri 1 Sukodono Jepara, amounting to 22 students, consisting of 15 boys and 7 girls. This study uses classroom action research that consists of four stages: planning, action, observation and reflective. The research instrument using the observation sheet to record the attitudes and events that take place in learning. In this classroom action research, analysis technique used is descriptive techniques percentage form. In the first cycle of learning from as many as 13 students 22 students have achieved mastery while 9 students who have not completed and the second cycle as many as 20 students have achieved mastery learning while unfinished 2 students.Conclusions based on the results of the research data that the increase in the high jump learning through games.formula 1 circuit in SD Negeri 1 Sukodono is satisfactory.